Partisipasi Masyarakat dalam Pembangunan Fisik di Desa Gumuk Kecamatan Licin Kabupaten Banyuwangi - Afrida Nur Laili; Khotibin Khotibin (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine (1) community participation in planning, physical development in Gumuk Village, Licin District, Banyuwangi Regency, (2) community participation in physical implementation in Gumuk Village, Licin District, Banyuwangi Regency, (3) community participation in evaluating physical development in the village. Gumuk Licin District, Banyuwangi Regency. This type of research includes field research, namely research conducted on the actual community or the field of community life which aims to collect data/information about certain problems regarding the lives of the people who are the object of research. This study also describes/unveils data and also analyzes to obtain clarity and truth about actions that have been empowered by the community, through data collection techniques of observation, interviews, and documentation. Data analysis in this study uses interactive model analysis from Miles and Huberman which includes the stages of data reduction, data presentation and data verification or drawing conclusions. The results of the study show that (1) Community participation in physical development planning in Gumuk Village is classified as good, this can be seen from the number of people who participate in the development planning Deliberation (Musrenbang) as evidenced by showing evidence of the attendance list of the Gumuk Village community, (2) Participation the community in implementing physical development in Gumuk village can be seen from the large number of donations in the form of mutual cooperation and donations of money or materials as well as their expertise, which is a form of community social support in accepting the results of development in a responsible manner, (3) Community participation in evaluating physical development in the village Gumuk Licin District, Banyuwangi Regency, can be seen from the many people who participate in evaluating the results of development through providing suggestions and criticisms to the village government as input for the next development.